The Influence of Service Differentiation and Customer Trust on Customer Loyalty with Digital Marketing as an Intervening Variable at PT. Anugerah Berkah Indonesia - Siti Ulfah; Hadiah Fitriyah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine the effect of service differentiation and customer trust on customer loyalty, with digital marketing as an intervening variable at PT. Anugerah Berkah Indonesia. This research adopts a quantitative approach using a survey method, where data were collected through questionnaires distributed to customers of PT. Anugerah Berkah Indonesia. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results indicate that service differentiation and customer trust have a positive and significant effect on customer loyalty. In addition, service differentiation and customer trust also have a positive and significant influence on digital marketing. However, digital marketing does not have a significant effect on customer loyalty. These findings suggest that customer loyalty is more strongly driven by core factors such as service uniqueness and customer trust rather than direct digital marketing activities. In this study, digital marketing functions as a supporting communication tool but has not yet become a primary determinant in shaping customer loyalty. The findings imply that companies should prioritize strengthening service differentiation and customer trust as key strategies to enhance customer loyalty, while integrating digital marketing as a complementary tool to reinforce value communication and customer engagement effectively.